2009
DOI: 10.1121/1.3068442
|View full text |Cite
|
Sign up to set email alerts
|

Considering distortion product otoacoustic emission fine structure in measurements of the medial olivocochlear reflex

Abstract: In humans, when the medial olivocochlear ͑MOC͒ pathway is activated by noise in the opposite ear, changes in distortion product otoacoustic emission ͑DPOAE͒ level, i.e., the MOC reflex, can be recorded in the test ear. Recent evidence suggests that DPOAE frequency influences the direction ͑suppression/enhancement͒ of the reflex. In this study, DPOAEs were recorded at fine frequency intervals from 500 to 2500 Hz, with and without contralateral acoustic stimulation ͑CAS͒ in a group of 15 adults. The MOC reflex w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 33 publications
(29 reference statements)
10
93
0
Order By: Relevance
“…The majority of investigators have reported DPOAE suppression during the presentation of contralateral noise in humans and amplitude level reduction in f DP within the range from 1 to 4 dB, depending on the frequency tested ( As shown in literature, DPgram frequency resolution clearly effects changes in DPOAE level at selected points of maxima and minima. For high frequency resolution, suppression occurs more often and is larger at fine-structure maxima, whereas enhancement of level is more likely to occur near the minima (Sun, 2008;Abdala et al, 2009). Frequency dependence of the DPOAE suppression is a consequence of the MOC effects providing frequency-specific inhibitory feedback in the wide frequency region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of investigators have reported DPOAE suppression during the presentation of contralateral noise in humans and amplitude level reduction in f DP within the range from 1 to 4 dB, depending on the frequency tested ( As shown in literature, DPgram frequency resolution clearly effects changes in DPOAE level at selected points of maxima and minima. For high frequency resolution, suppression occurs more often and is larger at fine-structure maxima, whereas enhancement of level is more likely to occur near the minima (Sun, 2008;Abdala et al, 2009). Frequency dependence of the DPOAE suppression is a consequence of the MOC effects providing frequency-specific inhibitory feedback in the wide frequency region.…”
Section: Discussionmentioning
confidence: 99%
“…Such interaction, which has such a strong effect, depends on frequency and leads to the ripple shapes of DPOAE fine structure, and accordingly to a large inter-and intra-subject variability of DPOAEs. This mechanism contributes to the complex differences in the DPOAE levels measured with or without CAS which may manifest themselves in the form of suppression or enhancement (Abdala et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Efferent activation affects the outer hair cells amplification and therefore the DPOAE level; hence, it might impact the OMEG estimates. It has been shown that the impact of efferents is minimal on the generator components in comparison with their effects on the composite DPOAEs (Abdala et al 2009;Henin et al 2011Henin et al , 2014. Furthermore, the efferents impact on the generator components is reduction of the level by upto 1.5 dB, while the efferent effect on the composite DPOAE is less systematic and can lead to enhancement or reduction of the level by about 5 dB (Henin et al 2011).…”
Section: Naghibolhosseini and Long: Estimation Of Round-trip Outer-mimentioning
confidence: 99%